Management of obstructed balloon catheters. Issue 6437 (14th July 1984) - Browning, G G; Barr, L; Horsburgh, A G
Abstract : Failure of a balloon catheter to deflate is not uncommon and prevents its removal. Methods of overcoming the problem include traction, bursting the balloon by overinflation, dissolving it with solvents, puncturing it percutaneously with a needle, or puncturing it with a wire stylet passed through the catheter. All except the last technique have major disadvantages and are of questionable safety. Transcatheter puncture of the balloon was used in 16 patients to remove obstructed balloon catheters without any technical difficulty, distress to the patient, or complication. The procedure is safe, simple, and does not require an anaesthetic. If necessary it could be performed safely by nursing or paramedical staff without the patient having to be admitted to hospital. It is the method of choice for the management of this problem.